Annual mean efficiency of the duct type OWC in regional ocean environments. (June 2022) - Trivedi, Kshma; Koley, Santanu
Abstract: This study investigates the annual average efficiency of the duct OWC-WEC in the regional irregular waves conditions. The OWC device is situated over a wrinkled bottom For the incident wave spectrum, the Bretschneider spectrum is used for the regional wave condition around the device plant. Further, the sea states associated with the regional wave condition in the site Pico, Portugal are considered. The yearly averaged efficiency of the duct OWC initially becomes higher when incident wavelength becomes shorter and reach to a maximum. Thereafter, the device efficiency declines for short waves. Further, for wider chamber, the efficiency becomes higher. For longer waves, the efficiency amplitude declines for higher front wall's draft, and an opposite tendency is formed for moderate and smaller incident waves.